2015
DOI: 10.1016/j.ijhydene.2015.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Improved resistance to hydrogen embrittlement of friction stir welded high carbon steel plates

Abstract: The hydrogen embrittlement of the friction stir welded high carbon steel plates was evaluated by the cathodic hydrogen charging method. The welding was performed below Ac1 transformation point and therefore the stir zone of the welds contained refined ferrite matrix distributed with cementite particles. After hydrogen charging for 4 hours, large quantities of irreversible dome-shaped blisters were formed on the surface of the base metal. However, no blisters were observed in the stir zone even after charging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…According to Sun and Fujii [11], higher resistance to hydrogen embrittlement was observed in the stirred region of the SK 4 high-carbon steel. The FSW process caused no phase transformation in the weld of SK 4 high-carbon steel and the stirred region (of the weld) consisted of a homogeneously refined ferrite matrix with evenly dispersed cementite particles [11].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to Sun and Fujii [11], higher resistance to hydrogen embrittlement was observed in the stirred region of the SK 4 high-carbon steel. The FSW process caused no phase transformation in the weld of SK 4 high-carbon steel and the stirred region (of the weld) consisted of a homogeneously refined ferrite matrix with evenly dispersed cementite particles [11].…”
Section: Introductionmentioning
confidence: 92%
“…According to Sun and Fujii [11], higher resistance to hydrogen embrittlement was observed in the stirred region of the SK 4 high-carbon steel. The FSW process caused no phase transformation in the weld of SK 4 high-carbon steel and the stirred region (of the weld) consisted of a homogeneously refined ferrite matrix with evenly dispersed cementite particles [11]. Fujii et al [12] revealed that the FSW process carried out on the ferriteaustenite two-phase region of carbon steels produced refined microstructure and the highest weld strength.…”
Section: Introductionmentioning
confidence: 92%
“…FSW does not significantly increase the hydrogen content in API 5 L X80 high strength pipeline steel during dry and underwater welding [1,9]. This suggests that FSW reduces the risk of hydrogen embrittlement in comparison to fusion welding processes during welding.…”
Section: Introductionmentioning
confidence: 93%
“…For pipeline steels, the influence of the hydrogen in the yield strength and tensile strength cannot be deemed significant [14,15,25,26]. Nevertheless, the ductility (fracture elongation) [14,27,28] and fracture toughness decrease significantly in hydrogen environments [9,12,[14][15][16][17][18][19][20][21][22][23][24]29]. In addition, the loss of ductility increases when the strength level of the steel is high [14,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation